A strategy tripod perspective on merger effectiveness in the higher education industry: the mediating role of future foresight - Sameer Sajwani, Zahraa (2021)
Purpose– The purpose of the study is to investigate the role of the strategy tripod premises, mediated by future foresight and its effect on merger effectiveness in the higher education industry. Design/methodology/approach–Aquantitative survey methodwas implemented, withthe data provided by senior managers of 14 universities that went through a merger from the years 2013–2016. The proposed model was tested using partial least squares (PLS) of structural equation modeling (SEM). Findings– The results indicate that government support, competitive intensity and knowledge creation capability relate positivity to merger effectiveness, and these relationships are mediated by future foresight competence. Originality/value– The study provides a better understanding of merger effectiveness in the higher education industry by identifying the role of future foresight competence in the application of strategy tripod and its contribution on merger effectiveness. Results indicate that future foresight competence contributes to the merger effectiveness and enables the effective implementation of the strategy tripod dimensions in higher education mergers.